2006
DOI: 10.1002/chem.200501538
|View full text |Cite
|
Sign up to set email alerts
|

Aryldithioethyloxycarbonyl (Ardec): A New Family of Amine Protecting Groups Removable under Mild Reducing Conditions and Their Applications to Peptide Synthesis

Abstract: The development of phenyldithioethyloxycarbonyl (Phdec) and 2-pyridyldithioethyloxycarbonyl (Pydec) protecting groups, which are thiol-labile urethanes, is described. These new disulfide-based protecting groups were introduced onto the epsilon-amino group of L-lysine; the resulting amino acid derivatives were easily converted into N alpha-Fmoc building blocks suitable for both solid- and solution-phase peptide synthesis. Model dipeptide(Ardec)s were prepared by using classical peptide couplings followed by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 89 publications
1
25
0
Order By: Relevance
“…We and others [44] have already observed that such a thiol is stable up to pH 7.5, and that its spontaneous decomposition is pH-dependant, the decomposition being spontaneous above pH 8.0, which is consistent with our results described herein.…”
Section: Resultssupporting
confidence: 95%
“…We and others [44] have already observed that such a thiol is stable up to pH 7.5, and that its spontaneous decomposition is pH-dependant, the decomposition being spontaneous above pH 8.0, which is consistent with our results described herein.…”
Section: Resultssupporting
confidence: 95%
“…Dipeptides for kinetic characterization were purchased when possible (e.g., Sigma, Bachem, Research Organics, Indofine, or MP Biochemicals), with the following exceptions: L-Ile-L-Phe was synthesized according to the procedure of Theodoropoulos and Craig (1955), and L-Lys-L-Phe was synthesized according to that of Lapeyre et al (2006). Syntheses for all other dipeptides are provided in Supplemental Data.…”
Section: Methodsmentioning
confidence: 99%
“…However, these probes have major limitations since they are unable to distinct apoptotic from necrotic cells, inasmuch as they penetrate into permeabilized necrotic cells and subsequently bind to phosphatidylserines that are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6 at the internal side of the cell membrane. More recently, other probes have been developed that directly target caspase-3 and become fluorescent only in the presence of active caspase-3, thus substantially increasing signal specificity (Bullok and Piwnica-Worms 2005;Lapeyre et al 2006). Functionality of these probes was demonstrated in human colon xenografts and in liver abscess mouse models (Bullok et al 2007), in isolated heart reperfusion injury (Pantos et al 2009) or after intra-dermal injection of caspase-3 (Zhang et al 2009).…”
mentioning
confidence: 99%